MANAJEMEN RISIKO KEBIJAKAN INFRASTRUKTUR PEMBANGUNAN DI INSTITUT TEKNOLOGI SUMATERA - Rifky Febrihanuddin Azis (Balitbangda Provinsi Lampung, 2020)
The acceleration of infrastructure development policy at the Sumatra Institute of Technology has the potential for risk so that the need for risk management. The purpose of this study is to find out how the risk management of infrastructure development policies at the Sumatra Institute of Technology. The research method used is concurrent explanatory with mixed methods approach. Data collection techniques gived questionnaires to 45 respondents and conducted interviews with 6 informants. The results of this research are significant risks based on technical feasibility aspects, namely a policy can run if staff can understand the policies that have been passed by 56.6% means medium risk, leaders and employees have many methods in implementing policies of 65.5% meaning high risk, institutions get support from 53.5% of the community and civil society means moderate risk. Significant risk based on political viability is a policy that can run if employees can understand the policy that has been approved by 49.4% means that the risk is moderate, leaders and employees have many methods in implementing the policy of 46.6% means that the risk is moderate, the dispute between the institution and the contractor is 62.7% meaning Tinggi risk, the institution has the support of the community and civil society by 59.4% means Sedang risk. Based on these results it can be concluded that risks can be mitigation by conducting socialization, coordination and communication between parties. Keywords : Acceleration Development, Risk Analysis, Risk Management